Modeling of natural-gas diffusion in oil-saturated tight porous media. (15th September 2021) - Hossein Doranehgard, Mohammad; Tran, Son; Dehghanpour, Hassan
Highlights: An analytical method is developed to calculate gas diffusion coefficient. During the soaking period, oil production rate ∝ 1 t . The oil produced during the soaking is less than 20% of the total produced oil. Abstract: In this paper, we propose a novel analytical solution to predict the diffusion coefficient and depth of natural gas penetration during soaking period of the cyclic gas injection process. Our analytical solution is derived by modeling gas-phase pressure declines using mass-balance and continuity equations. We model mass transport during the soaking period as a counter-diffusion process, and find that gas diffusion coefficient ( D ) and counter-current oil velocity are controlled by the pressure gradient at the early soaking times and by the gas concentration gradient when the soaking progresses. We calculate the depth of gas penetration in an oil-saturated core plug, and show that during the soaking period oil production rate ∝ t . In addition, the model can be used to predict the swelled oil volume by gas dissolution. We verified our model using the experimental data of C1 and a mixture of C1 and C2 with the molar ratio of 70/30 as the injected gas. The results reveal that D C 1 / C 2 D C 1 ≈ 2 . Finally, a thermodynamic consistency check was performed by comparing the amount of leaked-off gas in the experiments and that predicted by the model. The results show that these values are in the same range.